The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1177/08830738221144081
|View full text |Cite
|
Sign up to set email alerts
|

Association of NOD1 and NOD2 Polymorphisms With Susceptibility to Subacute Sclerosing Panencephalitis

Abstract: Background: Subacute sclerosing panencephalitis is a progressive neurodegenerative disease that is a late complication of measles infection. However, to date, the pathogenesis of subacute sclerosing panencephalitis is still not explained; both viral and host factors seem to be associated. The present study aimed to investigate the relationship between NOD1 and NOD2 gene variants and subacute sclerosing panencephalitis. Methods: The gene variants of NOD1 (rs2075820 and rs2075818) and NOD2 (R334Q and R334W) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
(33 reference statements)
0
1
0
Order By: Relevance
“…Interestingly, a case-control study found a genetic polymorphism in the NOD1 gene to be protective against SSPE. This is further attributed to a reduced capacity for the nod-like receptor encoded by this gene to activate NF-κB signalling upon recognition of pathogen-associated molecular patterns (50). It is possible that in SSPE, long-term diffuse activation of NF-κB, and thus chronic inflammation, may underlie the development and spread of tauopathy in genetically-vulnerable individuals.…”
Section: Subacute Sclerosing Panencephalitismentioning
confidence: 99%
“…Interestingly, a case-control study found a genetic polymorphism in the NOD1 gene to be protective against SSPE. This is further attributed to a reduced capacity for the nod-like receptor encoded by this gene to activate NF-κB signalling upon recognition of pathogen-associated molecular patterns (50). It is possible that in SSPE, long-term diffuse activation of NF-κB, and thus chronic inflammation, may underlie the development and spread of tauopathy in genetically-vulnerable individuals.…”
Section: Subacute Sclerosing Panencephalitismentioning
confidence: 99%